Integrated nutrient management for jute and allied fibre crops in Bangladesh: a review - Md Imran Ali; Sirajam Monira; Syed Nazrul Islam; Ronzon Chandra Das; Supti Mallick (Research in Agriculture Livestock and Fisheries, 2023)
Jute is well-known for its distinctive versatility in Bangladesh and comes in first place in terms of output, which illustrates the jute crop's dual character of quantity and quality. This review discusses the significance of the jute crop and the advantages of nutrient management techniques in the jute and allied fibre crops (JAF), which increase output, fecundity, and output to fulfill the nation’s potential fibre requirements. Due to the demand for JAF fibres in the production of various goods, fibres make a significant economic contribution to Bangladesh. It not only gives the rural population a job, but it also generates cash for the area. If integrated nutrient management strategies are used, it will be simple to meet future demand for jute-based products while still preserving agriculture. Res. Agric. Livest. Fish. Vol. 10, No. 2, August 2023: 183-188